Institutionalisation of academic integrity: Experiences at a distance education university in South Africa during COVID-19 - Marais, Ingrid (Critical Studies in Teaching and Learning, 2023)
Academic integrity is an ongoing concern in higher education. Research dating back to the 1960s shows students self-reporting cheating, and with the advent of more online education, concerns about the integrity of degrees have become even more widespread. Due to this concern about academic integrity, especially in view of the changes brought about by COVID-19, I launched a research project that aimed to holistically understand how academics understand and teach academic integrity and institutional policies around academic integrity, and how these policies are employed through analysing five years’ worth of student disciplinary records at a distance education university. I interviewed twenty-eight academics and academic managers and analysed sixty-six documents, as well as 3 383 student disciplinary records. Flowing from that larger project, I argue in this paper that there has not yet been institutionalisation of academic integrity at this university. I end by offering suggestions for how institutionalisation could occur.